Introduction of Exogenous Glycolate Catabolic Pathway Can Strongly Enhances Photosynthesis and Biomass Yield of Cucumber Grown in a Low-CO2 Environment - Chen, Zhi-feng; Kang, Xiu-ping; Nie, Hong-mei; Zheng, Shao-wen; Zhang, Tian-li; Zhou, Dan; Xing, Guo-ming; Sun, Sheng (Frontiers in Plant Science, 2019)
CO2 is very important for photosynthesis of green plants. CO2 concentration in the atmosphere is relatively stable, but it drops sharply after sunrise due to the tightness of the greenhouse and the absorption of CO2 by vegetable crops. Vegetables in greenhouses are chronically CO2 starved. To investigate the feasibility of using genetic engineering to improve the photosynthesis and yield of greenhouse cucumber in a low CO2 environment, five genes encoding glyoxylate carboligase (GCL), tartronic semialdehyde reductase (TSR), and glycolate dehydrogenase (GlcDH) in the glycolate catabolic pathway of Escherichia coli were partially or completely introduced into cucumber chloroplast. Both partial pathway by introducing GlcDH and full pathway expressing lines exhibited higher photosynthetic efficiency and biomass yield than wild-type (WT) controls in low CO2 environments. Expression of partial pathway by introducing GlcDH increased net photosynthesis by 14.9% and biomass yield by 44.9%, whereas the expression of the full pathway increased seed yield by 33.4 % and biomass yield by 59.0%. Photosynthesis, fluorescence parameters, and enzymatic measurements confirmed that the introduction of glycolate catabolic pathway increased the activity of photosynthetic carbon assimilation-related enzymes and reduced the activity of photorespiration-related enzymes in cucumber, thereby promoting the operation of Calvin cycle and resulting in higher net photosynthetic rate even in low CO2 environments. This increase shows an improvement in the efficiency of the operation of the photosynthetic loop. However, the utilization of cucumber of low concentration CO2 was not alleviated. This study demonstrated the feasibility of introducing the pathway of exogenous glycolate catabolic pathway to improve the photosynthetic and bio-yield of cucumber in a low CO2 environment. These findings are of great significance for high photosynthetic efficiency breeding of greenhouse cucumber.